In utero exposure to violence and child health in Iraq - Sulin Sardoschau (Journal of Population Economics, 2024)
Abstract This paper examines the impact of exposure to violence during pregnancy on anthropometric and cognitive outcomes of children in the medium run. I combine detailed household-level data on more than 36,000 children with geo-coded information on civilian casualties in the aftermath of the US invasion of Iraq between 2003 and 2009 and exploit within-mother differences in prenatal exposure to violence. I find that one violent incident during pregnancy decreases height- and weight-for-age z-scores by 0.13 standard deviations and lowers cognitive and behavioral skills of children. Leveraging information on the severity, type and perpetrator of violence, I isolate the effect of stress from access to prenatal care. The analysis reveals that stressful events, particularly those involving direct threats to personal safety (violence directed at the civilian population and involving execution and torture), exert an even larger negative impact on child health than those incidents that disrupt health infrastructure and access to prenatal care.
Additional information: I12;J13;O15
Keywords: 330; Stress; Child health; Iraq